Adverse Effects Associated with Protein Intake above the Recommended Dietary Allowance for Adults. (18th July 2013) - Delimaris, Ioannis
Abstract : Background . While high-protein consumption—above the current recommended dietary allowance for adults (RDA: 0.8 g protein/kg body weight/day)—is increasing in popularity, there is a lack of data on its potential adverse effects. Objective . To determine the potential disease risks due to high protein/high meat intake obtained from diet and/or nutritional supplements in humans. Design . Review. Subjects . Healthy adult male and female subjects. Method . In order to identify relevant studies, the electronic databases, Medline and Google Scholar, were searched using the terms:"high protein diet, " "protein overconsumption, " "protein overuse, " and "high meat diet." Papers not in English were excluded. Further studies were identified by citations in retrieved papers. Results . 32 studies (21 experimental human studies and 11 reviews) were identified. The adverse effects associated with long-term high protein/high meat intake in humans were (a) disorders of bone and calcium homeostasis, (b) disorders of renal function, (c) increased cancer risk, (d) disorders of liver function, and (e) precipitated progression of coronary artery disease. Conclusions . The findings of the present study suggest that there is currently no reasonable scientific basis in the literature to recommend protein consumption above the current RDA (high protein diet) for healthy adults due to its potential disease risks. Further research needs to be carried out in this area, including large randomized controlled trials.